Perception of music as a model of cognition of a musical work. - Tsuranova, Oksana; Haleeva, Оlena; Zeninets, Liliya (My University, 2020)
У статті вивчаються питання щодо процесу сприйняття музики як умовної моделі пізнання музичного твору.
Tsuranova O. Perception of music as a model of cognition of a musical work / O. Tsuranova О. Haleeva, L. Zeninets // Modern science : problems and innovations : abstracts of the 3rd International scientific and practical conference SSPG Publish. (Stockholm, Sweden , 1-3 June, 2020). – Stockholm, 2020. – P. 315–320.
Keywords: музичний твір, читання нот із листа, музичне мистецтво, музичне сприйнятті; piece of music, sight-reading, musical art, musical perception; музыкальное произведение, чтение нот с листа, музыкальное искусство, музыкальное восприятие